Differential abundance of sarcoplasmic proteome explains animal effect on beef Longissimus lumborum color stability. (April 2015) - Canto, Anna C.V.C.S.; Suman, Surendranath P.; Nair, Mahesh N.; Li, Shuting; Rentfrow, Gregg; Beach, Carol M.; Silva, Teofilo J.P.; Wheeler, Tommy L.; Shackelford, Steven D.; Grayson, Adria; McKeith, Russell O.; King, D. Andy
Abstract: The sarcoplasmic proteome of beef Longissimus lumborum demonstrating animal-to-animal variation in color stability was examined to correlate proteome profile with color. Longissimus lumborum (36 h post-mortem) muscles were obtained from 73 beef carcasses, aged for 13 days, and fabricated to 2.5-cm steaks. One steak was allotted to retail display, and another was immediately vacuum packaged and frozen at − 80 °C. Aerobically packaged steaks were stored under display, and color was evaluated on days 0 and 11. The steaks were ranked based on redness and color stability on day 11, and ten color-stable and ten color-labile carcasses were identified. Sarcoplasmic proteome of frozen steaks from the selected carcasses was analyzed. Nine proteins were differentially abundant in color-stable and color-labile steaks. Three glycolytic enzymes (phosphoglucomutase-1, glyceraldehyde-3-phosphate dehydrogenase, and pyruvate kinase M2) were over-abundant in color-stable steaks and positively correlated ( P < 0.05) to redness and color stability. These results indicated that animal variations in proteome contribute to differences in beef color. Highlights: Proteome basis of animal-to-animal variation in beef color stability was examined. Glycolytic enzymes were over-abundant in color-stable Longissimus lumborum steaks. Three glycolytic enzymes were positively correlated to redness and color stability. Differences in sarcoplasmic proteome contribute to beef color stability variations.